A-Posteriori Error Estimates for Uniform $p$-Version Finite Element Methods in Square (Advances in Applied Mathematics and Mechanics, 2018)
In this work, the $a$-$posteriori$ error indicator with an explicit formula for $p$-versionfinite element methods in square is investigated, and its reliable and efficientproperties are deduced. Especially, this $a$-$posteriori$ error indicator is determined by theright hand item of the model. We reformulate this $a$-$posteriori$ error indicator with finitecoefficients, which can be easily calculated during applications.